2021
DOI: 10.22270/jddt.v11i5-s.5086
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Degradation Kinetic study of Bilastine in Solution State by RP-HPLC Method

Abstract: Aim: The current study dealt with the degradation behavior of Bilastine and degradation kinetics of a drug in solution state. Background:  Very limited information on the effect of pH on maximum stability has been published. In order to understand the degradation kinetics of bilastine, aqueous stability studies were carried out, because such studies on bilastine have not been reported in the literature, further no methods have reported about shelf-life determination of bilastine. The study design involves sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The available literature review revealed a variety of methods for analyzing BIL in bulk or pharmaceutical formulations. The methods that have been published for the analysis of BIL were spectrophotometric [5][6][7], uorometric [8], HPLC [9][10][11][12], hydrophilic interaction liquid chromatographic method [4], HPTLC [13], Near-infrared spectroscopy [14], and electrochemical methods [15]. The HPLC technique needs a lot of extremely pure organic solvents, takes a long time to prepare samples, uses complicated apparatus, and, in certain situations, requires very expensive detectors.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature review revealed a variety of methods for analyzing BIL in bulk or pharmaceutical formulations. The methods that have been published for the analysis of BIL were spectrophotometric [5][6][7], uorometric [8], HPLC [9][10][11][12], hydrophilic interaction liquid chromatographic method [4], HPTLC [13], Near-infrared spectroscopy [14], and electrochemical methods [15]. The HPLC technique needs a lot of extremely pure organic solvents, takes a long time to prepare samples, uses complicated apparatus, and, in certain situations, requires very expensive detectors.…”
Section: Introductionmentioning
confidence: 99%
“…In general, chromatographic analytical methods require expensive detectors and ultra-pure solvents, in addition to the long time spent on sample preparation and extraction. Such costs may limit the application of chromatographic methods in quality control laboratories [13][14][15][16][17][18][19][20]. On the other hand, spectrophotometric methods suffer from low sensitivity, which limits their application in analyzing biological fluids [6][7][8].…”
mentioning
confidence: 99%
“…Through extensive literature review, various analytical techniques have been developed to analyze bilastine in both bulk form and pharmaceutical formulations. These techniques include spectrophotometric [6][7][8], spectrofluorimetric [9][10][11][12], high-performance liquid chromatographic [13][14][15][16][17][18][19], high-performance thin-layer chromatographic [20], near-infrared spectroscopic [21], and electrochemical methods [22].…”
mentioning
confidence: 99%